Pakistan: A study of market's returns and anomalies - Sana Tauseef; Philippe Dupuy (Journal of Economics, Finance and Administrative Science, 2022)
Purpose - This paper aims to expand foreign investors' understanding of potential return enhancement and risk diversification advantages offered by equity market of Pakistan through comparing its performance to performances in other markets and investigating what matters for investing in Pakistan's market. Design/methodology/approach - Comparative analysis of Pakistan Stock Exchange is performed using data for 22 developed and 22 emerging markets over the period 1993-2019. Cross-sectional analysis is performed using data for 130 non-financial firms from Pakistan and Carhart (1997) and Fama and French (2015) models are applied. The role of liquidity with five-factor model is analyzed using turnover rate and Amihud (2002) illiquidity cost as liquidity measures. Findings - Pakistan's equity offers substantial diversification benefits if added to developed market portfolios. However, observed large returns come together with inverted premia for most traditional factors indicating that investors may want to invest preferably in big stocks with low book-to-market and momentum. Finally, global investors can invest in high yielding stocks with low liquidity risk owing to positive connection between liquidity and returns. Practical implications - This study will provide investment model for foreign investors to enhance their portfolio returns. Policy makers in Pakistan must identify regulatory steps to facilitate foreign investments. Originality/value - To the best of the authors' knowledge, this is the first study which identifies efficiency gains offered by Pakistan's equity for global investors.
Keywords: G11; G12; G15; 330; Diversification; Factors; Liquidity; Pakistan